1997
DOI: 10.1126/science.275.5303.1113
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Force in Running Turkeys: The Economy of Minimizing Work

Abstract: During running, muscles and tendons must absorb and release mechanical work to maintain the cyclic movements of the body and limbs, while also providing enough force to support the weight of the body. Direct measurements of force and fiber length in the lateral gastrocnemius muscle of running turkeys revealed that the stretch and recoil of tendon and muscle springs supply mechanical work while active muscle fibers produce high forces. During level running, the active muscle shortens little and performs little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
709
7
13

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 675 publications
(756 citation statements)
references
References 21 publications
27
709
7
13
Order By: Relevance
“…Of course, if that is the case it is difficult to explain how a muscle can contribute to external work (De Haan et al 1989). Roberts et al (1997), however, showed that in the gastrocnemius muscle of turkeys who ran on the level, no stretch of the contractile elements occurred. Furthermore, Kram and Taylor (1990) based their cost-ofgenerating-force hypothesis on the idea that during level running the contractile elements of the muscle operate isometrically.…”
Section: Discussionmentioning
confidence: 93%
“…Of course, if that is the case it is difficult to explain how a muscle can contribute to external work (De Haan et al 1989). Roberts et al (1997), however, showed that in the gastrocnemius muscle of turkeys who ran on the level, no stretch of the contractile elements occurred. Furthermore, Kram and Taylor (1990) based their cost-ofgenerating-force hypothesis on the idea that during level running the contractile elements of the muscle operate isometrically.…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, it is possible that leg sti¡-ness adjustments indirectly result from the control of a lower level neuromuscular parameter (e.g. minimizing muscle ¢bre displacement during ground contact; (Roberts et al 1997). Further studies exploring the link between muscle^tendon action and leg sti¡ness should provide a better physiological understanding of leg sti¡-ness adjustments during running.…”
Section: Discussionmentioning
confidence: 99%
“…During running, there is little energy saved by pendular-energy conservation because the gravitational potential energy and kinetic energy of the COM fluctuate in phase. Instead, the spring-like properties of muscles and tendons in the stance phase of running result in an exchange between the kinetic energy of the COM and the elastic energy stored in these tissues (Cavagna et al 1964(Cavagna et al , 1977Ker et al 1987;Roberts et al 1997). At fast speeds, when the inverted-pendulum mechanism of walking is impaired, this bouncing gait provides a highly effective means of reducing the metabolic cost of locomotion.…”
Section: Introductionmentioning
confidence: 99%